PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERPERSPEKSTIF ISLAM RAHMATAN LIL ’ALAMIN ( IRA) : Studi Penanaman Nilai-Nilai Pendidikan Multikultural Di SMA Negeri 1 Ponorogo - Kasmui Kasmui; Happy Susanto; Anip Dwi Saputro (TARBAWI:Journal on Islamic Education, 2019)
This study examines the role and about the lack of education in implementing an integrated learning in the attitude of values namely; matter (mutual, cooperative, tolerant, peaceful, and the importance of mutually cherish each other as citizens of Indonesia.  So much happening the case split either internally or fellow adherents of Islam to other faiths or externally, there is even an indication of students embraced the radical leftism. Then the researchers in terms of giving the title of the research "Implementation study Islamic studies perspekstifly Islam rahmatan lil'alamin (IRA): study of the cultivation of the values of Multicultural Education in SMA Negeri 1 Ponorogo. In this study used qualitative approaches to research methodology. The process of data collection done by interviewing teachers of Islamic education, teacher PPkn, and also the head of the school. The material results of the interview will be analyzed and the results of the analysis of the results of the findings gave rise to Islamic Concepts namely Rahmatan Lil'alamin, applied SMAN 1 Ponorogo refers to 2013 in which curriculum contains close to learning that is practiced and live, practise honest behavior, discipline, courtesy, caring (mutual, cooperative, tolerant, peaceful), responsible, respontif, and pro-actively interact effectively in accordance with the development of the children in the neighborhood, family, school, society and nature around the State, nation, region and International Education in the perspective of Islam Rahmatan lil alamin.